Menc Handbook of musical cognition and development - Colwell, Richard (Oxford Oxford university press, 2006)
Answering fundamental questions about musical preference, ability, and communication, the field of Musical Cognition and Development is critical to the understanding of how music is processed, grasped, and learned. Drawn from the widely acclaimed New Handbook of Research on Music Teaching and Learning (Oxford, 2002), the MENC Handbook of Musical Cognition and Development covers the latest theoretical and practical techniques that explain meaning and understanding in music. A distinguished team of internationally recognized experts offers cogent and concise insights providing readers up-to-date information and references. The volume covers the most important topics in this field, including skill development in music performance, research on communicating music expressiveness, the neurobiology of music, the cognitive constraints in the listening process, and music and medicine as applied to neuroscience.Practical and affordable, this volume will prove essential for students and scholars of music education and the psychology of music. It is both an excellent starting point for those looking to gain an orientation to the field, and an up-to-date presentation of the most recent research findings for experienced researchers, instructors, and pedagogues.